Spectral theory of unidirectional transducers - DANICKI, E. (Archives of Acoustics, 2005)
A spectral theory of single-phase unidirectional transducers of the surface acoustic waves is presented. It helps to evaluate the stop-band width where the directionality takes place, and allows one to optimize the transducer structure in order to obtain its symmetric frequency response, with maximum directionality at the stop-band center.